The Intention of Using Cell Phones In Digital Banking Service Base on External Factors and Internal Factors - Winny Puspasari Thamrin; Kristiana Dewayani; Feny Fidyah (International Journal of Research in Counseling and Education, 2020)
The growing of digital services in the world of banking and the use of cellular telephones by customers, banks provide services in the form of phone and SMS banking that makes it easier for customers to transaction. The existence of digital banking makes it easy and saves time in making transactions. The purpose of this study was to examine the intention of using cell phones in digital banking services base on external factors (easiness, benefit, trust and risk) and internal factors (self efficacy and locus of control). This research model is prepared based on the concept of risk perception and behavior. Respondents in this study were 98 respondents that consist of students and employees. The sampling technique is non-random sampling. SEM model analysis techniques (structural equation model) with the help of the Lisrell 8.7 program. The results of this study indicate that the data obtained in accordance with the proposed model for both internal and external factors influence the intention of using cell phones for digital banking services.